Cartilage‐Specific Near‐Infrared Fluorophores for Biomedical Imaging1. Issue 30 (10th June 2015) - Hyun, Hoon; Owens, Eric A.; Wada, Hideyuki; Levitz, Andrew; Park, GwangLi; Park, Min Ho; Frangioni, John V.; Henary, Maged; Choi, Hak Soo
Abstract A novel class of near‐infrared fluorescent contrast agents was developed. These agents target cartilage with high specificity and this property is inherent to the chemical structure of the fluorophore. After a single low‐dose intravenous injection and a clearance time of approximately 4 h, these agents bind to all three major types of cartilage (hyaline, elastic, and fibrocartilage) and perform equally well across species. Analysis of the chemical structure similarities revealed a potential pharmacophore for cartilage targeting. Our results lay the foundation for future improvements in tissue engineering, joint surgery, and cartilage‐specific drug development.